Influence of Texture on Drainability, Splash and Spray in Flexible Pavements - Jose Manuel Sanz Garcia; Manuel Romana Garcia; Jose Antonio Ramos Garcia (The Baltic Journal of Road and Bridge Engineering)
Although the splash and spray phenomenon produced by heavy trucks on road pavements is not a significant issue in relation to traffic safety, it may cause considerable inconveniences for those driving cars or motorbikes. This paper addresses the issue of pavement engineering with regard to surface characteristics; particularly pavement texture and its influence on water mobilization and projection in conditions of wet weather and heavy traffic. Considering the theoretical concept of pavement macrotexture, the analysis starts with the hypothesis concerning a relationship between Mean Profile Depth (MPD) and water splashed during rain. In order to focus on the impact of texture on splash and spray, a field experiment was carried out to test the hypothesis using 5 test tracks on a range of different pavement textures. The experiment was performed using a Traffic Speed Drain Meter (TSDM), which is a new drainability survey device presented to PIARC for approval. This equipment employs the laser and image technology and allows one to simultaneously obtain MPD and water splash data. The results of drainability and MPD were compared for each test track. Having analysed the pavements with different MPD ranges in the experiment, it has been concluded that MPD and water splashed apparently have an inversely proportional relationship. In addition, the TSDM proved to be a suitable equipment (repeatability) at an affordable cost (high performance of data collection). Finally, it has been concluded that there is a way to reduce splash and spray adjusting the infrastructure rather trying to solve the issue modifying vehicle moving modes. Therefore, if the issue is properly addressed by civil engineers and road managers, road safety in the areas of heavy rain may be improved at an affordable cost. The experiment presented here is considered a starting point opening the path for further research.